Insulin-Producing Cells Derived from Human Embryonic Stem Cells: Comparison of Definitive Endoderm- and Nestin-Positive Progenitor-Based Differentiation Strategies - Wei, Rui; Yang, Jin; Hou, Wenfang; Liu, Guoqiang; Gao, Meijuan; Zhang, Lin; Wang, Haining; Mao, Genhong; Gao, Hongwei; Chen, Guian; Hong, Tianpei (PLOS ONE, 2013)
Human embryonic stem cells (hESCs) are pluripotent and capable of undergoing multilineage differentiation into highly specialized cells including pancreatic islet cells. Thus, they represent a novel alternative source for targeted therapies and regenerative medicine for diabetes. Significant progress has been made in differentiating hESCs toward pancreatic lineages. One approach is based on the similarities of pancreatic β cell and neuroepithelial development. Nestin-positive cells are selected as pancreatic β cell precursors and further differentiated to secrete insulin. The other approach is based on our knowledge of developmental biology in which the differentiation protocol sequentially reproduces the individual steps that are known in normal β cell ontogenesis during fetal pancreatic development. In the present study, the hESC cell line PKU1.1 was induced to differentiate into insulin-producing cells (IPCs) using both protocols. The differentiation process was dynamically investigated and the similarities and differences between both strategies were explored. Our results show that IPCs can be successfully induced with both differentiation strategies. The resulting IPCs from both protocols shared many similar features with pancreatic islet cells, but not mature, functional β cells. However, these differently-derived IPC cell types displayed specific morphologies and different expression levels of pancreatic islet development-related markers. These data not only broaden our outlook on hESC differentiation into IPCs, but also extend the full potential of these processes for regenerative medicine in diabetes.